Postnatal changes in maternal and neonatal plasma antioxidant vitamins and the influence of smoking. Issue 1 (1st January 2002) - Bolisetty, S; Naidoo, D; Lui, K; Koh, T H H G; Watson, D; Montgomery, R; Whitehall, J
Abstract : Objective: To study the postnatal changes in the plasma concentrations of fat soluble antioxidant vitamins and malondialdehyde (MDA) in mothers and their newborns and their relation to smoking. Design: Prospective cohort study. Setting: Tertiary perinatal centre. Subjects: Eighteen non-smoking and 14 smoking mothers and 33 infants. Main outcome measures: Plasma concentrations of vitamins E, A, and β-carotene and MDA were measured in mothers and infants at delivery and on day 4 post partum. Results: Neonatal plasma levels of vitamins E, A, and β-carotene were significantly lower than maternal levels both at delivery and on day 4 in both groups. There was a significant postnatal increase in plasma vitamin E levels in smoking mothers and neonates of both groups. A significant postnatal increase in maternal, but not neonatal, plasma vitamin A was noted in both groups. Cord plasma vitamin E levels were significantly lower in infants of smoking mothers (mean 4.7 v 6.5 μmol/l, p = 0.041). Plasma MDA was paradoxically lower in smoking mothers at delivery (3.19 v 4.01 μmol/l, p = 0.03) and on day 4 (1.37 v 3.29 μmol/l, p = 0.005) and in infants of the smoking group on day 4 (2.18 v 3.12 μmol/l, p = 0.014). Also, there was a significant postnatal fall in plasma MDA levels on day 4 in mothers and infants in the smoking group. Conclusions: The postnatal changes in plasma vitamin E were more pronounced in the smoking group. The postnatal changes in plasma vitamins A and β-carotene were similar in both groups. The rapid decline in plasma MDA in smoking mothers and their infants suggests withdrawal of oxidative stress from smoking around delivery. This coincided with the increase in plasma vitamin E.